N-acyl-ω-aminoaldehydes are efficient substrates of plant aminoaldehyde dehydrogenases - Frömmel, Jan; Šebela, Marek; Demo, Gabriel; Lenobel, René; Pospíšil, Tomáš; Soural, Miroslav; Kopečný, David (Amino acids, 2015)
Plant aminoaldehyde dehydrogenases (AMADHs, EC 1.2.1.19) belong to the family 10 of aldehyde dehydrogenases and participate in the metabolism of compounds related to amino acids such as polyamines or osmoprotectants. Their broad specificity covers ω-aminoaldehydes, aliphatic and aromatic aldehydes as well as nitrogen-containing heterocyclic aldehydes. The substrate preference of plant AMADHs is determined by the presence of aspartic acid and aromatic residues in the substrate channel. In this work, 15 new N-acyl derivates of 3-aminopropanal (APAL) and 4-aminobutanal (ABAL) were synthesized and confirmed as substrates of two pea AMADH isoenzymes (PsAMADH 1 and 2). The compounds were designed considering the previously demonstrated conversion of N-acetyl derivatives as well as substrate channel dimensions (5-8 Å × 14 Å). The acyl chain length and its branching were found less significant for substrate properties than the length of the initial natural substrate. In general, APAL derivatives were found more efficient than the corresponding ABAL derivatives because of the prevailing higher conversion rates and lower K m values. Differences in enzymatic performance between the two isoenzymes corresponded in part to their preferences to APAL to ABAL. The higher PsAMADH2 affinity to substrates correlated with more frequent occurrence of an excess substrate inhibition. Molecular docking indicated the possible auxiliary role of Tyr163, Ser295 and Gln451 in binding of the new substrates. The only derivative carrying a free carboxyl group (N-adipoyl APAL) was surprisingly better substrate than ABAL in PsAMADH2 reaction indicating that also negatively charged aldehydes might be good substrates for ALDH10 family.
Keywords: molekulární struktura; Aldehyde Dehydrogenase; Molecular Structure; aldehydy; hrách setý; simulace molekulového dockingu; propylaminy; Pisum sativum; aldehyddehydrogenasa; substrátová specifita; kinetika; Propylamines; Substrate Specificity; Molecular Docking Simulation; Kinetics; Plant Proteins; Aldehydes; rostlinné proteiny